Tagpi the Kamuning textile arts center - Boncan, Camille Isabel B.; Madrid, Dolores Cecilia T. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
This study explores the capacity of disprogrammed, transprogrammed, and cross-programmed architecture to revitalize communities, by providing unique solutions and interventions that conventional building typologies may not be able to address. It begins with thorough research on a selected area of study ; which in this case is the Kamuning community. Many know Kamuning for its tela market, and bespoke clothing industry. However, it seems that less have realized that the area has not progressed as much as its surroundings. The market, along with the rest of the Kamuning community has been physically overshadowed by its surroundings, and left to deteriorate. And because of this, Kamuning's textile industry has been neglected. Disadvantaged groups now exist in the community. Using an agenda-based design approach, a mix of commercial, educational, and technical spaces were created especially for the revitalization of Kamuning's textile arts industry. Generally, the study aims to shed light on how the Kamuning market could best be utilized. Like an actual patch, Tagpi is made to strengthen Kamuning's textile arts industry, and become the emblem of this craft in the country.
Best Thesis (Architecture) AY 2016-2017, 2nd place
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Textile industry and fabric -- Kamuning (Quezon City)